The Influence of Service Quality and Brand Image on Customer Loyalty At the Post Office in Batam City - Syahrul Bahri; Wasiman Wasiman (Jurnal Impresi Indonesia, 2026)
This research aims to investigate and analyze the influence of Service Quality and Brand Image on Customer Loyalty at the post office in Batam City, specifically in the context of parcel delivery services. This research employs a quantitative approach using primary data collected through a questionnaire. The sample consisted of 100 customers who used postal services in Batam City in 2025, selected using the Slovin formula. The data were analyzed using multiple linear regression with the assistance of SPSS version 25. The results of this study indicate that Service Quality has a positive and significant effect on Customer Loyalty. Similarly, Brand Image also has a positive and significant effect on Customer Loyalty. Furthermore, the F-test results show that Service Quality and Brand Image simultaneously have a significant effect on Customer Loyalty at the post office in Batam City. The findings confirm that both service quality and brand image play crucial roles in shaping customer loyalty. Improving service quality and strengthening brand image can effectively enhance customer loyalty. Therefore, the post office in Batam City should focus on these factors to maintain and increase customer loyalty.